Association between coeliac disease and cardiovascular disease: a prospective analysis in UK Biobank - Conroy, M; Allen, N; Lacey, B; Littlejohns, T (BMJ Publishing Group, 2023)
Objectives: To investigate whether people with coeliac disease are at increased risk of cardiovascular disease, including ischaemic heart disease, myocardial infarction, and stroke.